Metalloporphyrin-based porous polymers prepared via click chemistry for size-selective adsorption of protein. Issue 11 (24th July 2018) - Zhu, Dailian; Qin, Cunqi; Ao, Shanshi; Su, Qiuping; Sun, Xiying; Jiang, Tengfei; Pei, Kemei; Ni, Huagang; Ye, Peng
Abstract: Zinc porphyrin-based porous polymers (PPs-Zn) with different pore sizes were prepared by controlling the reaction condition of click chemistry, and the protein adsorption in PPs-Zn and the catalytic activity of immobilized enzyme were investigated. PPs-Zn-1 with 18 nm and PPS-Zn-2 with 90 nm of pore size were characterized by FTIR, NMR and nitrogen absorption experiments. The amount of adsorbed protein in PPs-Zn-1 was more than that in PPs-Zn-2 for small size proteins, such as lysozyme, lipase and bovine serum albumin (BSA). And for large size proteins including myosin and human fibrinogen (HFg), the amount of adsorbed protein in PPs-Zn-1 was less than that in PPs-Zn-2. The result indicates that the protein adsorption is size-selective in PPs-Zn. Both the protein size and the pore size have a significant effect on the amount of adsorbed protein in the PPs-Zn. Lipase and lysozyme immobilized in PPs-Zn exhibited excellent reuse stability.